Health at work: Indicators and determinants. A revised literature and data review for Germany - Julia Schneider; Miriam Beblo (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2010)
In this paper, the current knowledge and issues regarding the economic impact of health at work in Germany is reviewed as a part of the EU project's. An inquiry into health and safety at work: a European Union perspective's (acronym: HEALTHatWORK). After a description of the German institutional framework for occupational safety and health (OSH), it presents indicators of health and safety at work's such as sickness absences, occupational accidents and diseases, disability rents, working conditions, and OSH policy. The paper's major contribution is a review of economic research on the determinants of OSH indicators in Germany, and a review of the data sets that have been or may be used. The aim is to identify the main issues addressed in the literature, the approaches adopted, the data analyzed, and the research gaps that still exist with respect to analyzing health at work in Germany. – – Die Studie bietet einen Überblick über den Forschungsstand zu Sicherheit und Gesundheitsschutz am Arbeitsplatz (occupational safety and health, OSH) in Deutschland und dient damit als Grundlage für den deutschen Beitrag zum EU Koordinationsprojekt 'An inquiry into health and safety at work: a European Union perspective'. Nach einer Beschreibung der in Deutschland für OSH verantwortlichen Institutionen präsentiert die Studie das in Deutschland erreichte Arbeitsschutzniveau durch einschlägige Indikatoren - wie krankheitsbedingten Fehlzeiten, Berufsunfällen und -krankheiten, Erwerbsunfähigkeitsrenten, Arbeitsbedingungen und OSH-Strategien. Der Hauptbeitrag dieser Studie liegt in der Darstellung des aktuellen ökonomischen Forschungsstandes zu Determinanten von OSH-Indikatoren sowie der verwendeten und verwendbaren Datenquellen für Deutschland. Ziel ist, die der Literatur inhärenten Fragestellungen, Methoden, Datengrundlagen und Ergebnisse aufzuzeigen und verbleibende Forschungslücken im Bereich Gesundheit und Arbeit zu identifizieren.
Keywords: I18; J80; 330; occupational safety and health; Arbeitsschutz; Betriebliches Gesundheitsmanagement; Deutschland